Structural and Photoluminescent study of Glutathione ZnS:Ce Nanoparticles (International Journal of Food and Nutritional Sciences, 2022)
Using microwave method synthesis of uncapped and GSH capped ZnS doped with trivalent Ce ions. The effect of GSH as a capping agent on the structural and optical activty was studies at different concentrations. The presence of GSH on the ZnS:Ce surface was identified by spectroscopic techniques like FTIR. Increase in the concentration of GSH helped us for the synthesis of small sized ZnS:Ce nanoparticles. Information regarding structure and particle size was collected from XRD patterns the nanoparticles showed ZnS cubic structure with size between 3.5-3.0 nm. The cubical nature of these nanoparticles was further confirmed by lattice fringes and SAED patterns with bright circular rings. Effect of capping agent was studied by TEM images, were the size was found to be 8 nm for uncapped and 4 nm for capped nanoparticles with spherical nature. EDAX measurement showed the incorporation of Ce ions in the -doped ZnS nanoparticles and quantum confinement was observed from absorption spectra through blue-shift with reduction in the size of these nanoparticles. Photoluminescence studies for the entire investigated samples displayed two emission bands one in UV (360 nm) and the other at visible region (600 nm). The result showed enhanced luminescence property was observed in the case of capped nanoparticles compare to uncapped.